Influence of sulfur source on properties of CuSbS2 particles. (1st November 2022) - Liu, Liu; Zhao, Yijie; Zhi, Guowei; Cao, Lihui; Wang, Wei; Sun, Luanhong; Che, Yuxuan
Abstract: CuSbS2 is a direct p-type semiconductor with a two-dimensional layered structure of orthorhombic system, excellent electrical performance, and a band gap of 1.1–1.5 eV, which has a light absorption coefficient of more than 10 4 cm −1 in the visible light range. CuSbS2 particles were synthesized by microwave irradiation method, and the effects of different sulfur sources on the phase structure, morphology and electrochemical performance of CuSbS2 particles were studied. The results showed that the sample prepared by thiourea as sulfur source was CuSbS2 phase, and the morphology was composed of flower-like microspheres and rod-like particles. However, nanorod-like CuSbS2 particles were obtained using L-cysteine or 3-thiopropionic acid as sulfur sources, and the phase of samples contained CuSbS2 and Sb2 S3 phase. Electrochemical tests showed that L-cysteine based CuSbS2 particles had the largest photocurrent response, a photocurrent density of 1.03 μ A cm −2 and impedance of 14.66 Ω.